Recent Trends of Interventional Pain Management as Minimally Invasive Procedure - Philothra, Petrina Theda; Irham, Lalu Muhammad (Scripta Medica, 2025)
Interventional pain management is crucial as a minimally invasive procedure because it offers targeted therapy, reduces opioid dependence, provides rapid and long-lasting relief, is less risky, has fewer side effects, enhances function and healing and is supported by clinical evidence and guidelines. A bibliometric study in interventional pain management aims to provide a comprehensive overview of the research landscape, highlighting trends, key topics and gaps in knowledge that can inform future studies and clinical practices. The use of bibliometric tools in pain management studies has evolved to include more advanced methodologies, increased global participation and a focus on specific pain types. The integration of software visualisation tools and the use of various bibliometric indicators have enhanced the ability to analyse and understand the utilisation of interventional pain management research landscape. The compilation of data which were retrieved from Scopus database from 2014-2024. A total of 13,606 publications (100 % in English) with topic interventional pain management as minimally invasive procedure from 2014-2024 were retrieved covering 3,313 sources with total authors 63,460. The number of publications showed a noticeable increase starting in the early 2016 with the peak at 2022. The most relevant sources for documents include BMJ Open (954 documents), followed by Archives of Physical Medicine and Rehabilitation (353 documents), PM and R (264 documents) and Pain Physician (237 documents). Recent trends in interventional pain management, particularly focusing on minimally invasive techniques are characterised by a significant increase in publication frequency, emphasis on targeted and non-destructive treatments and improved clinical outcomes. These factors collectively highlight the importance and growing recognition of these methods in modern pain management practices.
Keywords: Bibliometrics; Pain management; Minimally invasive surgical procedures; Physical and rehabilitation medicine